Vinyl Acetate Modified Scots Pine Reinforced HDPE Composites: Influence of Various Levels of Modification on Mechanical and Thermal Properties - Ozmen, Nilgul; Cetin, Nihat Sami; Mengeloglu, Fatih; Birinci, Emre (BioResources, 2013)
In order to compare the effect of vinyl acetate modification (VA) at different levels of weight percentage gain, Scots pine wood flour was modified with VA to three different wt% gains (10%, 16%, and 21% WPGs). Acetic anhydride (AA) modification at 24% WPG was also studied. Modified Scots pine wood flour reinforced HDPE composites (WPCs) were produced at 30 wt% wood flour loading by using extrusion-injection molding process and the mechanical properties of WPCs were determined. The thermal and morphological properties of WPG were characterised by using TGA and SEM techniques. The increase in tensile strength was significant for VA modified WPCs in comparison to the AA modified, unmodified or neat HDPE composites. Thermal stability was also significantly improved with increasing the WPG levels of VA modification.
Keywords: 3. Good health